Shaping Consumer Preferences: The Role of a Portuguese State-Owned Company in Fish Nutritional Education (European Journal of Marketing and Economics, 2024)
A fundamental human need is ensuring an adequate diet for energy and metabolic function. This paper examines Docapesca – Portos e Lotas, SA, a Portuguese state-owned company in the fish sector, highlighting its proactive role in consumer nutritional education, a strategy with significant marketing and economic implications. Portugal's high fish consumption, ranking third globally, underscores the importance of this initiative, given fish's rich nutritional profile including high-quality protein, essential vitamins A and D, and vital Omega-3 fatty acids. While Docapesca's core functions include organizing the first sale of fish on mainland Portugal and supporting the fishing harbor sector, a key objective is to influence consumer preferences through nutritional education and knowledge transfer regarding healthy food and diet. This encompasses social responsibility, quality assurance, societal cooperation, and environmental stewardship as integral to its mission. Drawing on privileged state information and in-depth interviews with key decision-makers, this study analyzes Docapesca's strategies. Findings, based on data from the entire Portuguese population with a focus on younger generations (16-34 years old), reveal a profound shift in consumer perception: Portuguese consumers now view fish as more than a commodity, recognizing its enhanced value stemming from Docapesca's educational efforts. This demonstrates how state-led initiatives can positively shape market demand and consumer behavior for health-promoting products.
Keywords: Consumer Behavior, Nutritional Marketing, Public Policy, Food Economics, Brand Perception, State-Owned Enterprises, Fish Market